Challenges of an English Teacher in Teaching at The Best School in a Rural Area - Marhamah; Ari Prasetyaningrum; M. Adib Nazri; Siti Ayu Surayya (Journal of Classroom Action Research, 2026)
This study aims to identify the challenges faced by an English teacher and the strategies used to overcome them at MA NWDI Lepak, recognized as the best school in a rural area of East Lombok. Using a qualitative descriptive approach, this research explored the teacher’s real experiences through classroom observation, semi-structured interviews, and documentation. The findings revealed three major challenges in English teaching: low student motivation, varied levels of language proficiency, and limited learning facilities. To address these, the teacher implemented adaptive strategies such as brainstorming, elicitation, scaffolding, group learning, differentiated support, and delayed error correction. These approaches demonstrated creativity and student-centered teaching that fostered learning despite infrastructural constraints. The study concludes that the success of English teaching in rural schools depends not on advanced facilities but on the teacher’s creativity, innovation, and adaptability, and recommends that rural teacher development programs emphasize context-based pedagogical training to enhance effective, communicative, and contextualized English instruction.